Genome-wide association studies of metabolites in Finnish men identify disease-relevant loci - Yin, Xianyong; Chan, Lap Sum; Bose, Debraj; Jackson, Anne U.; VandeHaar, Peter; Locke, Adam E.; Fuchsberger, Christian; Stringham, Heather M.; Welch, Ryan; Yu, Ketian; Fernandes Silva, Lilian; Service, Susan K.; et al. (Nature communications, 2022)
Few studies have explored the impact of rare variants (minor allele frequency < 1%) on highly heritable plasma metabolites identified in metabolomic screens. The Finnish population provides an ideal opportunity for such explorations, given the multiple bottlenecks and expansions that have shaped its history, and the enrichment for many otherwise rare alleles that has resulted. Here, we report genetic associations for 1391 plasma metabolites in 6136 men from the late-settlement region of Finland. We identify 303 novel association signals, more than one third at variants rare or enriched in Finns. Many of these signals identify genes not previously implicated in metabolite genome-wide association studies and suggest mechanisms for diseases and disease-related traits. The Finnish population is enriched for genetic variants which are rare in other populations. Here, the authors find new genetic loci associated with 1391 circulating metabolites in 6136 Finnish men, demonstrating that metabolite genetic associations can help elucidate disease mechanisms.